Simplified Characterization of Building Thermal Response Rates. (November 2015) - Dong, Ziqian; Zhu, Pai; Bobker, Michael; Ascazubi, Marco
Abstract: Building thermal response rates refer to those dynamic conditions when a building interior is not held in steady-state by the operation of its HVAC systems. A method is proposed and preliminary results demonstrated for using data available from the typical large-building Building Automation System (BAS) to automatically characterize temperature response rates at the zone level. The work described employs a data-based "black-box" inverse-model approach. It is proposed that such empirically derived response rates could then inform building control algorithms for optimization associated with building commissioning and on- going control over the operations phase of the building's life-cycle. The paper reports on work being conducted collaboratively by teams of engineers and computer scientists at New York Institute of Technology and the City College of New York.